2003
DOI: 10.1128/jvi.77.3.1927-1939.2003
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class II Polymorphisms and Susceptibility to Recurrent Respiratory Papillomatosis

Abstract: Recurrent respiratory papillomatosis (RRP) is characterised by multiple laryngeal papillomas. Left untreated, the lesions enlarge, spread, and endanger the airway. Medical treatments are unsatisfactory, and repeated surgery remains the mainstay of therapy. RRP is caused by human papillomavirus (HPV) infection. However, since oral HPV infection is common and RRP is rare, other host and/or viral factors may contribute to pathogenesis. In an attempt to identify such factors, we have investigated 60 patients. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 43 publications
3
50
2
1
Order By: Relevance
“…Therefore such precise quantitative comparison was not possible in our study. The overall HPV genotype prevalence in our study group was consistent with data published earlier, demonstrating that HPV6 and HPV11 are the dominant types in JORRP patients (12,16,20); however, in our study more cases of HPV11-related papillomas were observed (70%), whereas it was previously reported that the predominant genotype in JORRP patients was HPV6 (19). This may be due to the particular HPV epidemiology seen in our Polish population.…”
supporting
confidence: 44%
See 1 more Smart Citation
“…Therefore such precise quantitative comparison was not possible in our study. The overall HPV genotype prevalence in our study group was consistent with data published earlier, demonstrating that HPV6 and HPV11 are the dominant types in JORRP patients (12,16,20); however, in our study more cases of HPV11-related papillomas were observed (70%), whereas it was previously reported that the predominant genotype in JORRP patients was HPV6 (19). This may be due to the particular HPV epidemiology seen in our Polish population.…”
supporting
confidence: 44%
“…It has also been proposed that genes coding for HLA II may play a role in JORRP development. Different HLA II alleles were identified, and a worse RRP course was seen in homozygotes bearing ''defective'' alleles (12).…”
mentioning
confidence: 99%
“…This same study found preliminary evidences for an HLA-DRB1*14 association in juvenileonset disease and a HLA-B*27 association in adult-onset disease [135] . Another study confirmed the association between HLA-DRB1*03: 01 and the severity of the disease in Caucasian patients and found also a positive association with DRB1*01: 02, DQB1*02: 01 and DQB1*02: 02 and a protective effect for DQB1*06: 02 [136] .…”
Section: Recurrent Respiratory Papillomatosismentioning
confidence: 61%
“…However, it is still unclear whether HPV causes this alteration in immunity or if children with impaired immunity develop RRP. As well as the susceptibility to cervical cancer caused by HPV has been related to some specific HLA alleles, similarly it has been seen that this association is fulfilled in patients with RRP, where certain alleles influence the course of the disease, favoring the severity [8][9][10] or, on the contrary, fulfilling a protective role 11,12 .…”
Section: Introductionmentioning
confidence: 91%
“…HLA-DRB1*14 has been associated with susceptibility to JO-RRP, whereas HLA-DRB1*0301 with susceptibility to AO-RRP. Interestingly, patients homozygous for HLA-DRB1*0301 show a more severe clinical picture 8 . Also, it has been shown that the HLA-DQA and HLA-DQB1 alleles present in different proportions in children with RRP regarding their controls.…”
Section: Discussionmentioning
confidence: 99%